Análise das propriedades de fluxo de diferentes tipos de açúcar - Santos, Luana Cristina dos (Universidade Federal de São Carlos, 2017)
Various processes in food, pharmaceutical and chemical industries have to handle with solid particles at some point during their processes. From the manufacturing process to storage of these materials, interparticle forces may intensify and lead to serious issues as incrustation inside the equipment or blocking a silo output. Therefore, it becomes necessary a better understanding about particle systems flowability, which include a good physical chemistry characterization and morphology associated with flow parameters analysis that will help on the flowability prediction. The purpose of this work was to investigate the flowability of four types of sugars: icing sugar from União® (IS), granulated sugar from Colombo® (GS), very high polarization (VHP) sugar from São Martinho industry (VS) and refined sugar from União® (RS), through classical tests as repose angle and Hausner ratio and dynamic tests in rheometer. For particle characterization, sieving was conducted to obtain size distribution and scanning electron microscopy (SEM) for morphology visualization. GS and VS types presented to be more similar in shape and size, with crystal configuration and higher particle mean diameter. RS and IS, on the other hand, showed greater percentage of fines and irregular shape, where IS was the type with more agglomerates. Cohesive forces were more noticeable in the IS type since this is the sugar with the smallest grain size distribution. As a consequence, this presented a greater resistance to flow, with a Hausner ratio of 1,33 (good flowability is between 1.12-1.18) and the higher angle of repose of 40º. Dynamic shear tests were made in powder rheometer FT4 from Freeman Technology and returned uncertain data for GS and VS, evidencing that this equipment may not be suitable for this kind of material. Compressibility analysis always showed greater values in dynamic condition than static ones and despite of GS and VS similarities, GS and RS were closer in compaction kinetics due the related values of D90. Overall, one may say sugar IS had the worst flowability among the 4 types following by RS wich is the second with a greater number of fines. VS and GS were classified as free flow materials according to classical tests. However, powder rheometer presented some limitations to higher particle size (about 1 mm) materials analysis. On the other hand, as seen in classical tests, IS and RS showed similarity in some tests made using powder rheometer.
Flow properties analysis of different types of sugar
Keywords: Propriedades de fluxo; Ângulo de repouso; Índice de Hausner; Açúcar; Flow properties; Hausner ratio; Sugar; Angle of repose; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA